Effects of Spartina alterniflora invasion on the community structure and diversity of wetland soil bacteria in the Yellow River Delta. Issue 5 (7th May 2022) - Shang, Shuai; Hu, Shunxin; Liu, Xiaoxue; Zang, Yu; Chen, Jun; Gao, Ning; Li, Liangyu; Wang, Jun; Liu, Longxiang; Xu, Jikun; Zhang, Yumiao; Wu, Tao; et al.
Abstract: The exotic plant Spartina alterniflora is expanding rapidly along China's coast regions, seriously threatening native ecosystems. Soil bacteria are important for biogeochemical cycles, including those of carbon, nitrogen, and sulfur, in wetland ecosystems. There is growing evidence that microorganisms are important in case of plant invasion. In the present study, we studied the interlacing area of S . alterniflora and Suaeda heteroptera, selected soil of invaded and non‐invaded regions and explored the effect of the composition and diversity of bacterial communities in coastal wetlands. The bacterial community composition of invasive and noninvasive areas was subjected to high‐throughput sequencing. In the five areas tested, the main bacterial phyla were Proteobacteria, Bacteroides, and Acidobacteria; the richness of the bacterial community in the soil increased after S . alterniflora invasion, most changes occurred at the genus level. The relative abundances of Desulfobulbus and Sulfurovum were higher in invasive areas than in noninvaded areas. PCA, RDA, and LEfSe analyses found that the S . alterniflora invasion significantly influenced the bacterial community and physicochemical properties of wetland soil. In conclusion, soil microbial community composition was tightly associated with S . alterniflora invasion. This study provide an important scientific basis for further research on the invasion mechanism of S .  alterniflora . Abstract : Soil microbes are important for biogeochemical cycles of carbon, nitrogen, and sulfur in wetland ecosystems. There is growing evidence that microorganisms are important for plant invasion. We explored the functional role of microorganisms during the invasion of Spartina alterniflora in coastal areas of China.